Effect of Gender Based Violence on the Performance of Uganda Women Entrepreneurship Programme (Uwep) on Women in Uganda: A Case Study of Women in Nauyo Town Council Mbale City - Mugide Racheal (Uganda Christian University, 2024)
The study was conducted in Nauyo Town Council in Mbale City, in Eastern Uganda. This area has been considered appropriate given its proximity to the researcher and also has a number of women economic challenges with characteristics of gender based violence. This was after securing a placement letter which gave the student the authority to carry out her study from Nauyo community in Mbale City and it is a requirement that a student was supposed to compile a research report as proof which the student has complied. The Research report is in five chapters. In this study the researcher sought to establish the effect of gender based violence on the performance of Uganda Women’s Entrepreneurship Programme on women in Uganda, a case study of women in Nauyo Town Council, Mbale City. The objectives that guided the study were to establish the Effect of gender based violence on women’s access to economic resources in Nauyo Town Council, Mbale City, to find out effect of gender based violence on women’s use of economic resources in Nauyo Town Council, Mbale City and to know the Effect of gender based violence on the control of economic resources by women in Nauyo Town Council, Mbale City. The student learnt a lot of things through numerous assignments given to her, which exposed her to different life aspects within the course, the program as a result of interactions with different categories of people The student encountered some challenges in the course of the program which she was able to solve and overcome with the help of the supervisor and fellow students.